HASSKARL'S CINCHONA BARKS 1. HISTORICAL REVIEW - C. E. RIDSDALE; L. A. Anderson. A. T. Keene & J. I). Phi - - (REINWARDTIA, 1984)
The preliminary results of alkaloid analyses of Hasskaii's cinchona bark collection, made in Peru in 1852/3' is given, and the identity and historical aspects of the material discussed in respect of the role the plants played in the Javanese plantations.